Testicular Doses of Patients Undergoing Radiological Examination of the Chest at Federal Medical Centre Makurdi, Nigeria - Alumuku, L; Iortile, J.T; Agba, E.H (International Journal of Advances in Life Science and Technology, 2014)
The testicular dose of eight adult male patients undergoing radiological examination of the chest were investigated at the radiological department of the Federal Medical Center (FMC) Makurdi using themoluminescent dosimetry technique. The investigation was carried out using LiF TLD discs Reader, TLD model 4500 (Harshaw Radiation measurement product USA), 3-phase diagnostic X-ray machine and single a phase X-ray machine. The Mean testicular dose of the male patients investigated was found to be 0.0662±0.0034mGy. There is also a significant correlation between testicular dose and tube potential, in which higher tube potential delivered higher values of testicular doses. Results showed that, testicular doses are within acceptable limits, which is approximately 6.6% of the 1mGy reference dose level.